2015
DOI: 10.1186/s13024-015-0008-9
|View full text |Cite
|
Sign up to set email alerts
|

Active immunization against alpha-synuclein ameliorates the degenerative pathology and prevents demyelination in a model of multiple system atrophy

Abstract: BackgroundMultiple system atrophy (MSA) is a neurodegenerative disease characterized by parkinsonism, ataxia and dysautonomia. Histopathologically, the hallmark of MSA is the abnormal accumulation of alpha-synuclein (α-syn) within oligodendroglial cells, leading to neuroinflammation, demyelination and neuronal death. Currently, there is no disease-modifying treatment for MSA. In this sense, we have previously shown that next-generation active vaccination technology with short peptides, AFFITOPEs®, was effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
120
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 136 publications
(134 citation statements)
references
References 55 publications
(88 reference statements)
4
120
0
1
Order By: Relevance
“…Moreover, when administered to a transgenic model of MSA, AFF 1 also induced a reduction in neurodegeneration and demyelination in neocortex, striatum, and corpus callosum [65]. The clearance of α-syn induced by AFF 1 involved activation of microglia, increased anti-inflammatory cytokine production, and reduced spreading of α-syn to astroglial cells [65,66]. These studies suggested that vaccination with AFFITOPEs could help ameliorate the neurodegenerative pathology in synucleinopathies.…”
Section: Immunotherapy Targeting Aβmentioning
confidence: 91%
See 4 more Smart Citations
“…Moreover, when administered to a transgenic model of MSA, AFF 1 also induced a reduction in neurodegeneration and demyelination in neocortex, striatum, and corpus callosum [65]. The clearance of α-syn induced by AFF 1 involved activation of microglia, increased anti-inflammatory cytokine production, and reduced spreading of α-syn to astroglial cells [65,66]. These studies suggested that vaccination with AFFITOPEs could help ameliorate the neurodegenerative pathology in synucleinopathies.…”
Section: Immunotherapy Targeting Aβmentioning
confidence: 91%
“…These results suggested that α-syn vaccination is effective in reducing neuronal accumulation of α-syn aggregates and that further development of this approach might have a potential role in the treatment of synucleinopathies. Other active immunization approaches using AFFITOPEs (AFFiRiS AG) that mimic abnormal conformations of α-syn have been studied in animals model of PD and MSA [65,66]. AFFITOPEs that mimic the C-terminus region of α-syn are able to elicit an immune response specific to α-syn oligomers [66].…”
Section: Immunotherapy Targeting Aβmentioning
confidence: 99%
See 3 more Smart Citations